HUBUNGAN PENGETAHUAN DAN TINDAKAN IBU DENGAN PERKEMBANGAN MOTORIK HALUS ANAK USIA 4-6 TAHUN DI PAUD TIBAN INDAH IV, KELURAHAN TIBAN INDAH, KECAMATAN SEKUPANG - Yessy Oktasilfiya; Ibrahim Ibrahim (Universitas Batam, 2017)
The fine motor nerves development of the children is a characteristic related to the ability of children to perform movements which involves specific body parts with the motion of muscles and at the same time require rapid coordination to the brain. It is tremendously crucial matter for the mothers to be able to recognize the growth of their infants’ motor system. In this study, the researchers aim to examine the correlation of the 4 to 6 years old children mothers’ knowledge levels and their attitude in relation to the development of their children motor system particularly in Tiban Indah IV Pre-school of Sekupang in 2017. This study applied a descriptive analytic method of cross-sectional approach design. As the data instrument, the researchers spread the questionnaires which were completed by 40 respondents through total sampling technique. This study took a place as one month observation which was dated on June 2017. The result of the study reveals that 55% of mothers have good knowledge level on the development of their children motor system, conversely, 60% of mother’s have good attitude toward the development of their children motor system. This findings are strengthen by the result of the Chi-Square statistical test that indicates a significant correlation of the mother knowledge levels shown by (p = 0.001) as well as mother’s attitude noted by (p = 0.001).To conclude, there is a significant correlation between knowledge levels of 4 to 6 years old children mother’s and their attitude toward the development of the children motor systemin Tiban Indah IV Pre-school, Sekupang in 2017. Finally, it is expected that the mothers are able to improve their knowledge and awareness on the growth of their children, specifically on the development of their motoric system to perform movements of their body.